Size of lower jaw as an early indicator of skeletal class III development - Stojanović Zdenka; Nikodijević Angelina; Udovičić Božidar; Milić Jasmina; Nikolić Predrag (Vojnosanitetski Pregled)
Background/Aim. Malocclusion of skeletal class III is a complex abnormality, with a characteristic sagital position of the lower jaw in front of the upper one. A higher level of prognatism of the lower jaw in relation to the upper one can be the consequence of its excessive length. The aim of this study was to find the differences in the length of the lower jaw in the children with skeletal class III and the children with normal sagital interjaw relation (skeletal class I) in the period of mixed dentition. Methods. After clinical and x-ray diagnostics, profile tele-x-rays of the head were analyzed in 60 examinees with mixed dentition, aged from 6 to 12 years. The examinees were divided into two groups: group 1 - the children with skeletal class III and group 2 - the children with skeletal class I. The length of the lower jaw, upper jaw and cranial base were measured. The proportional relations between the lengths measured within each group were established and the level of difference in the lengths measured and their proportions between the groups were estimated. Results. No significant difference between the groups was found in the body length, ramus and the total length of the lower jaw. Proportional relation between the body length and the length of the lower jaw ramus and proportional relation between the forward cranial base and the lower jaw body were not significantly different. A significant difference was found in proportional relations of the total length of the lower jaw with the total lengths of cranial base and the upper jaw and proportional relation of the length of the lower and upper jaw body. Conclusion. Of all the analyzed parameters, the following were selected as the early indicators of the development of skeletal class III on the lower jaw: greater total length of the lower jaw, proportional to the total lengths of cranial base and the upper jaw, as well as greater length of the lower jaw body, proportional to the length of the upper jaw body. .